Interstitial Lung Disease in Immunocompromised Children - Gao, Xianfei; Michel, Katarzyna; Griese, Matthias (Diagnostics (Basel), 2022)
Background: The range of pulmonary complications beyond infections in pediatric immunocompromised patients is broad but not well characterized. Our goal was to assess the spectrum of disorders with a focus on interstitial lung diseases (ILD) in immunodeficient patients. Methods: We reviewed 217 immunocompromised children attending a specialized pneumology service during a period of 23 years. We assigned molecular diagnoses where possible and categorized the underlying immunological conditions into inborn errors of immunity or secondary immunodeficiencies according to the IUIS and the pulmonary conditions according to the chILD-EU classification system. Results: Among a wide array of conditions, opportunistic and chronic infections were the most frequent. ILD had a 40% prevalence. Of these children, 89% had a CT available, and 66% had a lung biopsy, which supported the diagnosis of ILD in 95% of cases. Histology was often lymphocyte predominant with the histo-pattern of granulomatous and lymphocytic interstitial lung disease (GLILD), follicular bronchiolitis or lymphocytic interstitial pneumonitis. Of interest, DIP, PAP and NSIP were also diagnosed. ILD was detected in several immunological disorders not yet associated with ILD. Conclusions: Specialized pneumological expertise is necessary to manage the full spectrum of respiratory complications in pediatric immunocompromised patients.